Expression analysis of the TRI5 gene of Fusarium graminearum in wheat and maize coleoptiles. (Jóvenes en la Ciencia, 2024)
The necrotrophic fungus F. graminearum is responsible for causing Fusarium head blight in wheat and ear rot in maize. This fungal infection leads to reduced crop yields and contamination of the crops with mycotoxins like trichothecene deoxynivalenol (DON), which can cause poisoning in animals and humans. The production of DON is facilitated by a set of genes, with the TRI5 gene encoding trichodiene synthase being a key player. While some factors that can activate the TRI5 gene in wheat are known, it's unclear whether this gene is activated when the fungus infects wheat or maize coleoptiles. This study reveals that using ammonium sulfate as a nitrogen source induces the expression of the TRI5 gene in minimal media. In wheat coleoptiles, F. graminearum forms infection structures at 5 days post-infection (dpi), where the induction of the TRI5 gene occurs. On the other hand, there is no TRI5 gene induction in maize coleoptiles. Finally, the TRI5 gene expression in plants was confirmed using semi-quantitative PCR, validating the induction in wheat coleoptiles at 5 dpi.